(untitled) (Gaceta Técnica, 2024)
The purpose of this research was to design a technological district of intelligent innovation for the industrial zones of the city of Barquisimeto, Venezuela. To support the information, an exhaustive bibliographic review was carried out that formed the theoretical bases for the design, and the result obtained in previous research to determine the urban and economic growth that can be strengthened by intelligent innovation technological districts, and their capacity to clustering space based on knowledge and talent. In the design process, the urban characteristics of the study area, land uses, road accessibility, service infrastructure, empty spaces, large universities, and potential for innovation attracting centers were considered. Subsequently, the areas of space clustering, design or planning axes and lines of intervention were identified to develop the urban design proposal characterized by the formation of four technology clusters connected by university brokers that attract and bring together companies, startups or SMEs that generate knowledge and innovation through the compaction of urban activities in the district